Hearing the Unheard: An Interdisciplinary, Mixed Methodology Study of Women’s Experiences of Hearing Voices (Auditory Verbal Hallucinations) - McCarthy-Jones, Simon; Castro Romero, Maria; McCarthy-Jones, Roseline; Dillon, Jacqui; Cooper-Rompato, Christine; Kieran, Kathryn; Kaufman, Milissa; Blackman, Lisa (Frontiers in Psychiatry, 2015)
This paper explores the experiences of women who ‘hear voices’ (auditory verbal hallucinations). We begin by examining historical understandings of women hearing voices, showing these have been driven by androcentric theories of how women’s bodies functioned, leading to women being viewed as requiring their voices be interpreted by men. We show the twentieth-century was associated with recognition that the mental violation of women’s minds (represented by some voice-hearing) was often a consequence of the physical violation of women’s bodies. We next report the results of a qualitative study into voice-hearing women’s experiences (N=8). This found similarities between women’s relationships with their voices and their relationships with others and the wider social context. Finally, we present results from a quantitative study comparing voice-hearing in women (n=65) and men (n=132) in a psychiatric setting. Women were more likely than men to have certain forms of voice-hearing (voices conversing) and to have antecedent events of trauma, physical illness, and relationship problems. Voices identified as female may have more positive affect than male voices. We conclude that women voice-hearers have and continue to face specific challenges necessitating research and activism, and hope this paper will act as a stimulus to such work.